Analisis Peningkatan Daya Saing IKM dengan Memanfaatkan Strategi Pemasaran Digital di Kabupaten Padang Lawas Utara - Aura Indah; Rina Irawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The rapid development of digital technology has created vast opportunities for Small and Medium Industries (SMIs) to enhance competitiveness and expand market reach. This community service program aims to assist SMI actors in Padang Lawas Utara Regency in understanding and implementing effective digital marketing strategies to strengthen their business position in the era of digital transformation. The method used includes training, mentoring, and evaluation activities involving ten SMI participants through a participatory approach. The training focused on utilizing social media platforms such as Instagram, WhatsApp Business, and TikTok as tools for product promotion, brand awareness improvement, and optimization of customer engagement. The results showed a significant increase in participants’ abilities to create engaging digital content, understand social media algorithms, and manage customer interactions professionally. However, challenges such as limited digital literacy, time management in media handling, and unequal technological infrastructure remain. Therefore, continuous support from local governments and educational institutions is needed to strengthen the digital capacity of SMI actors so they can adapt to modern market dynamics. Through the proper implementation of digital marketing strategies, SMIs have the potential to become key drivers of a competitive local economy.